Dynamic programming for an optimal and equitable public load shedding schedule - DEGLA, Guy; NDIAYE, Babacar; KAMPO, Mohamed (My University, 2018)
This paper provides a method for an optimal and equitable schedule of public load shedding on any time interval and any number of sectors. By combining dynamic programming and knapsack techniques, the method gives a schedule that iterates over particular intervals. Simulation results with respect to actual schedules of a local energy company show the potential of this new approach for solving such a general problem that challenges many energy worldwide companies.
Keywords: modeling; load shedding; dynamic programming; optimization; knapsack problem